Cassiel's servant - Carey, Jacqueline, 1964- (Tor, 2023)
"In Kushiel's Dart, a daring young courtesan uncovered a plot to destroy her beloved homeland. But hers is only half the tale. Now see the other half of the heart that lived it. Cassiel's Servant is a retelling of cult favorite Kushiel's Dart from the point of view of Joscelin, Cassiline warrior-priest and protector of Phèdre nó Delaunay. He's sworn to celibacy and the blade as surely as she's pledged to pleasure, but the gods they serve have bound them together. When both are betrayed, they must rely on each other to survive. From his earliest training to captivity amongst their enemies, his journey with Phèdre to avert the conquest of Terre D'Ange shatters body and mind... and brings him an impossible love that he will do anything to keep. Even if it means breaking all vows and losing his soul"--